Measuring Science: Performance Metrics and the Allocation of Talent - Sebastian Hager; Carlo Schwarz; Fabian Waldinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We study how performance metrics affect the allocation of talent. We exploit the introduction of a new measure of scientific performance: citation metrics. For technical reasons, the first citation database only covered citations from certain journals and years. Thus, only a subset of citations became visible, while others remained invisible. We identify the effects of citation metrics by comparing the predictiveness of visible to invisible citations. Citation metrics increased assortative matching between scientists and departments. We also find that highly-cited scientists in lower-ranked departments ("hidden stars") benefited from citation metrics, while minorities did not. Citation metrics also affected promotion decisions.
Keywords: J62; O31; J45; O31; J45; 330; performance metrics; allocation of talent; citations; scientists